Epidemiological evolution of dengue in the pre-pandemic to post-pandemic periods in the Americas and Brazil - Vivi-Oliveira, Viviane Karolina (2024)
Introduction: Dengue is an asymptomatic infection or present symptoms like low fever to disabling high fever, severe headache, retroocular, muscle and joint pain, in addition to skin rashes, and if associated with COVID-19, it can worsen the illness condition. Objective: investigate the epidemiological evolution of dengue in the pre-pandemic, pandemic and post-pandemic periods from an American and Brazilian perspective. Methodology: descriptive study, based on the search for information in epidemiological bulletins, data from DATASUS and the Pan American Health Organization/World Health Organization, in addition to articles available in databases provided by SciELO, ScienceDirect and Pubmed. Results: In the period before the pandemic, the high number of notifications was due to the DENV2 serotype, causing a large epidemic. In the years 2020-2021 there was a drop in the number of notifications due to the introduction of social and public health measures, misdiagnosis between the signs/symptoms of dengue and COVID-19, inaccurate serological tests and underreporting. In 2022 and 2023, the epidemiological scenario again points to increasing notification of dengue cases, mainly due to changes in routine vector control during the pandemic, combined with favorable environmental factors, such as increased rainfall. Conclusion: the neglect of both dengue fever and other diseases has negatively impacted the population today, since in order to mitigate the damage caused by the pandemic, actions to promote and prevent the health of endemic diseases in our territory, when placed in the background, have caused the underreporting of cases, influenced by changes in the political, economic and health spheres of society.